The Implementation of Depok Single Window Application Services to Fulfill Citizens’ Rights to Information - Adhitra, Reisya Zahra; Ridwan, Ridwan (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
This study investigates the implementation of the Depok Single Window (DSW) by the Depok City Government, aimed at providing city information services through a single application, viewed from the perspective of the public's right to information. Although DSW has the potential to fulfill this right, challenges in public awareness, adoption, and user experience complaints indicate that its implementation has not fully met expectations. This research evaluates DSW's success, considering aspects of communication, human resources, infrastructure, budget, bureaucratic structure, and implementation attitudes. A qualitative approach with descriptive analysis and case studies, involving in-depth interviews, observations, and literature reviews, was used. The results indicate several shortcomings, including significant deficiencies in communication and promotional strategies leading to low public awareness about DSW, a lack of budget for promotion and marketing hindering public adoption and engagement, and technical issues within the application, such as user interface challenges and system downtimes, limiting its effectiveness and user satisfaction. Despite these challenges, the study finds that policy implementers demonstrate strong support for DSW, showing commitment to its success and making efforts to address technical issues and improve user experience. However, to fully meet the public's right to information, the Depok City Government needs to enhance communication and promotional efforts, increase the budget for these activities, and make continuous technical improvements to ensure the application is reliable and user-friendly. Addressing these issues promptly will enable DSW to better fulfill its purpose.